Study on the development of rural poverty alleviation eco-tourism model based on internet technology - Ni Ma (MATEC Web of Conferences, 2022)
The Computer Internet technology has the advantages of strong gathering ability, wide coverage and so on. By giving full play to the advantages of computer technology, the relatively dispersed rural tourism resources can be effectively gathered together, to promote the vitality and value space of rural tourism in an all-round way, and to provide a new and reasonable way to solve the problem of poverty. This paper analyzes the rural poverty-alleviation eco-tourism model based on Internet technology from the perspectives of value and platform positioning, and discusses its development path in detail.